Nuclear Security Summits - Gill, Amandeep S. author. aut Link
XIII, 293 p. 1 illus.
Keywords: This book describes the four Nuclear Security Summits held over 2010-2016 at the initiative of U.S. President Barack Obama. The author draws upon his unique vantage point as a participant in the Summits, exclusive interviews with practitioners, and access to primary documents, to write an engaging history of the NSS and of nuclear security in general. The story of the NSS is also in part the story of multilateral nuclear forums, which have sprung up regularly since the dawn of the nuclear age to address perceived nuclear dangers. The success of these Summits in addressing the threat of nuclear terrorism holds important lessons for the design and work of nuclear forums today and into the future. The author presents a new approach to assessing ‘international learning’ that has important implications for the design of multilateral forums and updates the Cold War areas of nuclear knowledge being ‘learnt’ in the light of the NSS experience and other recent developments. This work willbe of interest to scholars and practitioners in security studies, nuclear history, and International Relations. Amandeep S. Gill is Visiting Professor at King's College London, UK, and Executive Director and Co-Lead of the Secretariat of the UN Secretary-General’s High-level Panel on Digital Cooperation, Geneva, Switzerland. .